1998
DOI: 10.1159/000026528
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Calcium and Potassium Currents by Lamotrigine

Abstract: Actions of the new antiepileptic drug lamotrigine (LTG) were characterized using extracellular and whole cell patch clamp recordings from rat CA1 and CA3 pyramidal cells in vitro. The results suggest that LTG, beside its previously described effect on the fast sodium inward current, also modulates – presumably voltage-gated – calcium currents and the transient potassium outward current ID. These may be effective mechanisms to inhibit pathological excitation in epilepsy and may be of potential benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 30 publications
1
28
2
2
Order By: Relevance
“…It thus seems unlikely that LTG-mediated inhibition of I A is due to its direct suppression of Ca 2+ current and the resultant decrease in intracellular Ca 2+ concentrations. This study seems to be inconsistent with previous reports showing that LTG might increase the amplitude of I A (6)(7)(8). The reason for this discrepancy is currently unknown.…”
Section: Discussioncontrasting
confidence: 99%
“…It thus seems unlikely that LTG-mediated inhibition of I A is due to its direct suppression of Ca 2+ current and the resultant decrease in intracellular Ca 2+ concentrations. This study seems to be inconsistent with previous reports showing that LTG might increase the amplitude of I A (6)(7)(8). The reason for this discrepancy is currently unknown.…”
Section: Discussioncontrasting
confidence: 99%
“…The most effective analgesics in our model were lamotrigine and flupirtine, both of which affect Na v and potassium channels [6,9]. Thus, it is plausible that rather than a subtype-selective effect on a particular isoform of Na v channels, the in vivo efficacy is a reflection of the combined pharmacological profile of a given compound on Na v , K v , and perhaps TRP channels relevant for signalling in pain pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Grunze et al (1998) and Zona et al (2002) reported that lamotrigine (100-500 μM) could increase a transient potassium current in hippocampus and cortex, respectively, although effects were small and required high drug concentrations. In a recent study, lamotrigine, again at relatively high concentrations (100-300 μM), was shown to inhibit the A-type potassium current in a hippocampal cell line, H19-7 (Huang et al 2004).…”
Section: Calcium Channel Inhibitionmentioning
confidence: 99%